Nghiên cứu chuyển hóa một số xeton -không no đi từ 2-hiđroxi-4-metoxiaxetophenon - Thảo và cộng sự, Nguyễn Minh (Vietnam Journal of Chemistry, 2014)
A series of pyrazoline derivatives have been prepared by reaction of a,b-unsaturated ketones (from 2-hydroxy-4-methoxyacetophenone) with p-nitrophenylhydrazine. These a,b-unsaturated ketones will be transformed to correspondent flavonoid - type compounds by the action of hydrogen peroxide (H2O2) in base condition. Structure of these products were confirmed by IR, 1H-NMR and MS spectroscopic data. Biological activities of these compounds have been investigated.